A Cross-Sectional Survey to Assess Biorisk Management System in Research and Diagnostic Laboratories in Khyber Pakhtunkhwa, Pakistan - Muhammad, Javed; Sarwar, Samreen; Khan, Tariq; Qasmi, Shamsul Arfin; Ikram, Aamer; Ahmad, Ghufran; Zahid, Maria; Durrani, Rida Haroon; Ahmed, Furqan (Frontiers in Public Health, 2021)
Financial, cultural, and managerial hurdles have made biosafety and biosecurity measures difficult in resource-constrained countries like Pakistan. Diagnostic and research laboratories have made significant advancements in biosafety and biosecurity in the last decade as a result of rising knowledge of bio risk management. As a result, the requirement to identify and close gaps has never been more important. The goal of this study was to analyse the current state of PPE, biosafety behavior, waste management, biosafety measures, biosecurity measures, training and safety, and health services in diagnostic and research laboratories across Pakistan's Khyber Pakhtunkhwa province. We adapted the WHO Laboratory Assessment tool (2012) and CWA 15793 (Biorisk management guidelines) for conducting a cross-sectional survey, which was distributed among various laboratories in KP. The data obtained from seven categories were analyzed using SPSS version 20.The survey included 31 laboratories, including 19 diagnostic and 19 research laboratories. In terms of PPE [x2=13.39, p=0.03], waste disposal [x2=23.32, p=0.05], and safety and health services [x2=65.92, p=0.05], there was a substantial difference between diagnostic and research labs. In comparison to diagnostic laboratories, all biorisk management practices were found to be appropriate in research labs. Our findings show that KPK laboratories have improved over time. However, based on the WHO and CWA 15793 recommendations, we were able to identify deficiencies that would necessitate significant improvements to the current setups. Organizations can use a KP snapshot of biorisk management to tailor their biosafety measures and training to solve the gaps found.